Organismal and Molecular Malacology 2017
DOI: 10.5772/68134
|View full text |Cite
|
Sign up to set email alerts
|

The Uniqueness of Achatina fulica in its Evolutionary Success

Abstract: The increasing load of environmental pollutants poses a serious threat over the globe. In this vulnerable situation, it is essential to have alternative sources of medicines, may be from invertebrates. Among invertebrates, although molluscs are known for their consumption as food and ethno-medicinal use, the importance of these animals is still overlooked. Presently attention has been geared toward molluscs including Achatina fulica which are now considered as one of the most evolutionary successful animals. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…As one of the most successful colonizers of terrestrial environments within Mollusca, giant African snails may possess advanced molecular mechanisms for host defence against biotic and abiotic stresses (Begum et al., 2000). Despite the fact that they lack the canonical vertebrate immunoglobulins, these snails have developed diverse repertoires of receptors, regulators and effectors (Mukherjee et al., 2017). Remarkably, the mucus system was reported to be one of the unique evolutionary modalities (Begum et al., 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the most successful colonizers of terrestrial environments within Mollusca, giant African snails may possess advanced molecular mechanisms for host defence against biotic and abiotic stresses (Begum et al., 2000). Despite the fact that they lack the canonical vertebrate immunoglobulins, these snails have developed diverse repertoires of receptors, regulators and effectors (Mukherjee et al., 2017). Remarkably, the mucus system was reported to be one of the unique evolutionary modalities (Begum et al., 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Within Mollusca, the clade Pulmonata includes several lineages that invaded the terrestrial zone and nonaquatic ecosystems, especially the Stylommatophora (Romero et al., 2016). The giant African snail, a species in the order Stylommatophora, is a representative of the group of land snails that have also developed fundamental morphological and physiological changes and behaviours, such as a pulmonate lung, complex immune system, mucus production and aestivation, that make it highly adapted to the terrestrial environment (Hiong et al., 2005; Mukherjee et al., 2017; Romero et al., 2016). Several reports on amphibious species have shown that the expansion and positive selection of genes related to innate immunity, nitrogen excretion, hormonal regulation and pulmonary surfactants were closely connected to the A‐T transition (Biscotti et al., 2016); however, the genomic features and evolutionary characteristics of terrestrial invertebrates remain poorly described.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most successful colonizers of terrestrial environments within Mollusca, giant African snails are remarkably adaptive and may possess advanced molecular mechanisms for host-defense against biotic and abiotic stresses 73 . Although giant African snails lack the canonical vertebrate immunoglobulin, they have developed diverse repertoires of receptors, regulators, and effectors 23 . To investigate the genes and pathways involved in immune and stress responses, we characterized the immune system on the basis of the genome of A. immaculata , including pattern recognition receptors, soluble factors, and mucus-related gene families (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have been working to understand their intricate immune system over the past few decades in order to collect useful chemicals to treat human diseases. It has been shown that Achatina has crucial immunological components such the coagulation system, innate immune molecules, bioactive proteins, and CRP ( 16 ). The evolutionary importance of Achatina having strong innate immune defences and infection-fighting abilities has also been noted ( 17 ).…”
Section: Phylogenetic History Of Crpmentioning
confidence: 99%